Transisi PAUD ke SD: Solusi Pendidikan Menyenangkan - Reza, Muhammad; Asbari, Masduki; Ely (Journal of Information Systems and Management (JISMA), 2024)
The goal is to transition children from Early Childhood Education (PAUD) to Primary School (SD) with an approach that emphasizes character development, social skills and language. The "Freedom to Learn" program views the importance of changing negative perceptions of learning at an early age, by focusing on enjoyable learning experiences. In the discussion, concrete steps were introduced to achieve the 6 foundational abilities in children, involving the roles of parents, teachers and partnerships with various parties. The transition from PAUD to SD is expected to be a meaningful moment, supporting children's character, and involving broad involvement from the community